Implementation of the Moving Class System in the Hadith Learning Process at MTsS MILBoS - Zikry Septoyadi; Vita Lastriana Candrawati; Dulyawit Naknawa; Agusalim (Yayasan Al Hidayah, 2026)
The moving class system is a strategy to improve the quality of learning, aiming to create a more engaging and innovative learning environment, and reduce student boredom. Furthermore, this system is designed to address the limited learning resources often found in static classrooms. The primary objective of implementing a moving class is to create an ideal educational environment by providing specially designed thematic classrooms equipped with various learning media tailored to the characteristics of each subject. In the context of Hadith learning, classrooms are specifically designed by providing educational games, television (TV), and reference books to enhance students' understanding and memorization of hadith. This study uses a qualitative approach with research subjects involving the principal, five teachers, and five students at MTsS Maghfirah Islamic Leadership Boarding School (MILBoS). This study aims to describe the empirical reality related to the implementation of the Moving Class System in Hadith learning at MTsS MILBoS. The results show that the role of teachers in implementing the moving class concept is not limited to being educators alone, but also as facilitators in the implementation of the system. Teachers are required to be more proactive and creative in managing classrooms and utilizing learning resources, particularly in adapting the room design to the characteristics of the subjects being taught. Infrastructure and learning media have proven to play a strategic role in supporting the teaching and learning process, so each classroom needs to be equipped with relevant media. This system is implemented through a class transfer mechanism every time a subject changes, so students learn in a space that has been tailored to their material needs.